Pemberdayaan Berbasis Pendidikan Keterampilan Membatik Untuk Peningkatan Kapasitas Perempuan Di LKP At - Tiqna - Istika Ayu Lestari; Albert Richart Singal; Sri Wahyuni; Mustangin Mustangin; A Ismail Lukman (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2022)
This study aims to examine in more depth how women's empowerment based on non-formal education in the development of batik skills in LKP -At – Tiqna. The approach to this research uses qualitative research. The method of data collection uses the method of interview, observation, study of documents. Data analysis is carried out using data reduction, data presentation, and drawing conclusions. Data validity techniques use source trangulation and triangulation techniques. The results of this research related to women's empowerment based on non-formal education are that there are several processes starting from awareness to increase women's interest in being involved in empowerment programs. The awareness process is carried out by identifying the needs to formulate needs that are used as a basis for program decision making. Next is mendorngong and invite women to participate in the program by socializing the program to the wider community. The knowledge transformation process is carried out with training as an effort to provide knowledge and skills for women that are adapted to women's conditions and carried out by material delivery methods and practices. Furthermore, assistance to increase women's independence in batik development.